Pengaruh Social Media Marketing, Service Quality Terhadap Customer Loyalty Dengan Brand Trust Dan Customer Satisfaction Sebagai Variabel Intervening Studi Pada Pengguna Gojek - Mochammad Rifqi Firmansyah; Sunarno Handoyo; Sutono Sutono (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to determine the influence of Social Media Marketing, Service Quality on Customer Loyalty, with Brand Trust and Customer Satisfaction as intervening variables. The variables in this study are Social Media Marketing, Service Quality, Brand Trust, Customer Satisfaction, and Customer Loyalty. This research uses a quantitative approach, based on the level of explanation, thus making it an associative research or a study that tests the influence between variables. The sample size consists of 180 respondents taken from the population of Gojek users in Indonesia, using purposive sampling technique. Data collection of variables was done using a questionnaire distributed through Google Form. Data analysis was conducted using Structural Equation Modeling (SEM) in the AMOS software. The results of this study are as follows: Social Media Marketing does not have a significant influence on Customer Loyalty, Service Quality does not have a significant influence on Customer Loyalty, Social Media Marketing has a positive and significant influence on Brand Trust, Social Media Marketing has a positive and significant influence on Customer Satisfaction, Service Quality has a positive and significant influence on Brand Trust, Service Quality has a positive and significant influence on Customer Satisfaction, Brand Trust has a positive and significant influence on Customer Satisfaction, Brand Trust has a positive and significant influence on Customer Loyalty, Customer Satisfaction has a positive and significant influence on Customer Loyalty. Brand Trust fully mediates the relationship between Social Media Marketing and Customer Loyalty, Customer Satisfaction fully mediates the relationship between Social Media Marketing and Customer Loyalty, Brand Trust fully mediates the relationship between Service Quality and Customer Loyalty, and Customer Satisfaction fully mediates the relationship between Service Quality and Customer Loyalty.